2021
DOI: 10.3389/fcell.2021.797026
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo: An Autoimmune Skin Disease and its Immunomodulatory Therapeutic Intervention

Abstract: Vitiligo is a chronic autoimmune depigmenting skin disorder characterized by patches of the skin losing functional melanocytes. Multiple combinatorial factors are involved in disease development, among which immune T cells play a prominent role. The immune cells implicated in melanocyte destruction through adaptive immunity include CD8+ cytotoxic T cells and regulatory T cells, and aberrantly activated skin-resident memory T cells also play a role in melanocyte destruction. Over the past several years, major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Vitiligo is an autoimmune disease in which melanocytes are destructed by autoreactive T cells, forming patches of unpigmented skin (Chang et al, 2021). In patients with vitiligo, melanocyte‐reactive T cells that recognize melanocyte differentiation antigens, including MLANA, TYR, and PMEL, are frequently found in perilesional skin and peripheral blood (Ongenae et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is an autoimmune disease in which melanocytes are destructed by autoreactive T cells, forming patches of unpigmented skin (Chang et al, 2021). In patients with vitiligo, melanocyte‐reactive T cells that recognize melanocyte differentiation antigens, including MLANA, TYR, and PMEL, are frequently found in perilesional skin and peripheral blood (Ongenae et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic T lymphocytes can induce cytotoxicity in melanocytes directly by releasing mediators such as TNF-α and IFN-γ. When IFN-γ binds to its receptor, the Janus kinase (JAK)/signal transducers and activators of transcription (STAT) pathway is activated and stimulates the transcription of the chemokine ligands CXCL9 and CXCL10 [ 53 ]. This creates a positive feedback loop for T-cell recruitment and function [ 53 ].…”
Section: Antioxidative Defense and Cellular Responses To Ros Accumula...mentioning
confidence: 99%
“…When IFN-γ binds to its receptor, the Janus kinase (JAK)/signal transducers and activators of transcription (STAT) pathway is activated and stimulates the transcription of the chemokine ligands CXCL9 and CXCL10 [ 53 ]. This creates a positive feedback loop for T-cell recruitment and function [ 53 ]. The levels of IFN-γ were reported to be elevated in lesional skin of patients with vitiligo [ 54 ], which induced an increase of CXCL10 in vitiligo melanocytes [ 55 ].…”
Section: Antioxidative Defense and Cellular Responses To Ros Accumula...mentioning
confidence: 99%
“…Keratinocytes were thought to be predominantly responsible for T cell recruitment and they were considered to produce the bulk of chemokines. [ 3 , 4 ] Few researchers pay attention to the pivotal role of fibroblasts in the pathogenesis of immunity in vitiligo. This study identified that IFNγ-responsive fibroblasts can recruit CD8 + T cells through CXCL9 and CXCL10 in vitiligo.…”
mentioning
confidence: 99%
“…This study sufficiently identified the positive-feedback loop between IFNγ-responsive fibroblasts and CD8 + T cells in vitiligo. Keratinocytes were thought to be predominantly responsible for T cell recruitment and they were considered to produce the bulk of chemokines [3,4] . Few researchers pay attention to the pivotal role of fibroblasts in the pathogenesis of immunity in vitiligo.…”
mentioning
confidence: 99%